2009
DOI: 10.1590/s1806-37132009001100010
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia nosocomial: importância do microambiente oral

Abstract: on average, 5-9 days the length of hospital stay of patients, nosocomial pneumonia markedly increases hospital costs. (5)(6)(7)(8) The use of oral antiseptic and antimicrobial agents to prevent nosocomial pneumonia has been widely studied and, based on what has been reported, the present study aimed to review the literature focusing on how oral microorganisms can influence the development of nosocomial pneumonia and on how the frequency of nosocomial pneumonia can be reduced by changing the oral environment. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
64

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 40 publications
0
32
0
64
Order By: Relevance
“…Studies of patients with mechanical ventilation in intensive care units showed that the oral cavity is an important reservoir of potentially pathogenic bacteria such as S. aureus, P. aeruginosa, and some Enterobacteriaceae (17)(18)(19). Dental plaque consists of a complex and dynamic biofilm formed on the supra-and subgingival surfaces of teeth, oral mucosa, and dorsum of the tongue.…”
mentioning
confidence: 99%
“…Studies of patients with mechanical ventilation in intensive care units showed that the oral cavity is an important reservoir of potentially pathogenic bacteria such as S. aureus, P. aeruginosa, and some Enterobacteriaceae (17)(18)(19). Dental plaque consists of a complex and dynamic biofilm formed on the supra-and subgingival surfaces of teeth, oral mucosa, and dorsum of the tongue.…”
mentioning
confidence: 99%
“…Other factors also predispose ICU patients to develop pneumonia, namely: the use of endotracheal tube, the deficient cleaning performed by the nursing team, as well as the complexity of the oral biofilm found on the patients' teeth and tongue and, mainly, in the ICU equipment [12,14,18,31,33].…”
Section: Dentistry In Icusmentioning
confidence: 99%
“…On the other hand, the microbiota of critically ill patients is composed of gram-negative microorganisms and highly-virulent strict anaerobes such as Streptococcus pneumoniae and Staphylococcus aureus, which are the potential etiologic agents of pneumonia [16,18,19,35].…”
Section: Main Health Issues Presented By Icu Patientsmentioning
confidence: 99%
See 2 more Smart Citations